Application of a Short-Term Hydrological Forecast System - Gökçen Uysal; Aynur Şensoy; A. Arda Şorman; M. Cansaran Ertaş (Doğal Afetler ve Çevre Dergisi)
This study aims to deploy a short term hydrological forecast system in snow dominated mountainous basins. The headwaters of Euphrates and Seyhan Basins, selected as study areas, stand out with their high water potential, snow melt feeding this potential and the presence of large and important water structures in the downstream. For the simulation of precipitation-runoff relationship, HBV model, a widely used model in the literature especially for mountainous regions, is utilized. Mesoscale Model 5 (MM5) and Weather Research and Forecast (WRF) model results are preferred as Numerical Weather Prediction (NWP) data. After calibration/validation of hydrological model parameters with observed precipitation, temperature and flow data, 1- and 2-day flow estimates are obtained using the analyzed NWP data as input. Hindcast simulations for the past period are implemented with a closed-loop structure on the Delft-FEWS platform, and performance evaluation is conducted by comparing them with streamflow observations. The results obtained may contribute to the more efficient operation of water structures located downstream of the basins and thus to the national economy.